Clinical significance of regional constructive and wasted work in patients receiving cardiac resynchronization therapy - Wang, Chun-Li; Wu, Lung-Sheng; Wu, Chia-Tung; Yeh, Yung-Hsin; Cheng, Yu-Wen; Yen, Kun-Chi; Chan, Yi-Hsin; Chuang, Chi; Kuo, Chi-Tai; Chu, Pao-Hsien (Frontiers in Cardiovascular Medicine, 2024)
Background Previous studies have shown that global constructive work (CW) and wasted work (WW) predict response to cardiac resynchronization therapy (CRT). This study evaluated the predictive value of regional CW and WW for reverse remodeling and clinical outcomes after CRT. Methods We performed a prospective study involving 134 CRT candidates with left bundle branch block and left ventricular ejection fraction ≤35%. Global and regional CW and WW were calculated using pressure-strain loop analysis. CRT response was defined by reverse remodeling as a reduction of ≥15% in left ventricular end-systolic volume after six months. Results At six-month follow-up, 92 (69%) patients responded to CRT. Of the regional CW and WW measures, lateral wall (LW) CW and septal WW were most strongly and significantly correlated with reverse remodeling. At multivariate analysis, LW CW and septal WW were both independent determinants of reverse remodeling. When LW CW and septal WW were included in the model, global CW and WW were not independently associated with reverse remodeling. LW CW and septal WW predicted reverse remodeling with an area under the curve (AUC) of 0.783 (95% CI: 0.700–0.866) and 0.737 (95% CI: 0.644–0.831), respectively. Using both variables increased the AUC to 0.832 (95% CI: 0.755–0.908). Both LW CW ≤878 mmHg% (HR 2.01; 95% CI: 1.07–3.79) and septal WW ≤181 mmHg% (HR 2.60; 95% CI: 1.38–4.90) were significant predictors of combined death and HF hospitalization at two-year follow-up. Conclusion LW CW and septal WW before CRT are important determinants of reverse remodeling and clinical outcomes.